2008
DOI: 10.1038/ng.229
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variant on 8q24 confers susceptibility to urinary bladder cancer

Abstract: We conducted a genome wide SNP association study on 1,803 Urinary Bladder Cancer (UBC) cases and 34,336 controls from Iceland and the Netherlands and follow up studies in seven additional case control groups (2,165 cases and 3,800 controls). The strongest association was observed with allele T of rs9642880 on chromosome 8q24, 30kb upstream of the c-Myc gene (allele specific OR=1.22; P=9.34×10−12). Approximately 20% of individuals of European ancestry are homozygous for rs9642880 (T) and their estimated risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
271
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(293 citation statements)
references
References 27 publications
16
271
3
3
Order By: Relevance
“…Another notable feature is that the SNPs are usually linked to one cancer type and not others. For example, rs13281615 is linked to breast cancer risk but not prostate or colon cancer (Easton et al 2007), and rs9642880 is linked to bladder cancer and not any other cancer types (Kiemeney et al 2008). However, there are some SNPs that can alter the risk for multiple cancer types such as rs6983267, which is associated with the risk of both prostate and colon cancer as well as others (Tomlinson et al 2007;Yeager et al 2007Yeager et al , 2008Wokolorczyk et al 2008;Curtin et al 2009).…”
Section: Myc and The Inherited Predisposition To Cancermentioning
confidence: 99%
“…Another notable feature is that the SNPs are usually linked to one cancer type and not others. For example, rs13281615 is linked to breast cancer risk but not prostate or colon cancer (Easton et al 2007), and rs9642880 is linked to bladder cancer and not any other cancer types (Kiemeney et al 2008). However, there are some SNPs that can alter the risk for multiple cancer types such as rs6983267, which is associated with the risk of both prostate and colon cancer as well as others (Tomlinson et al 2007;Yeager et al 2007Yeager et al , 2008Wokolorczyk et al 2008;Curtin et al 2009).…”
Section: Myc and The Inherited Predisposition To Cancermentioning
confidence: 99%
“…Several independent GWAS have implicated chromosome 8q24 as a hotspot for multiple epithelial cancers (2)(3)(4)(5)(6)(7). 8q24 contains at least three independent risk regions for prostate cancer (region 2: 128.14-128.28, region 3: 128.47-128.54, and region 1: 128.54-128.62); one region for colon cancer, which is the same as prostate cancer region 3; and a separate region for breast cancer (128.35-128.51) (4).…”
mentioning
confidence: 99%
“…For example, two meta-analyses that explored the relevance of GSTM1 null status on stomach cancer found a modest risk increase (La Torre et al, 2005;Saadat, 2006). A recent genome-wide association study identified a novel variant, which confers an increased risk for both urinary bladder and lung cancers (Kiemeney et al, 2008). These polymorphisms are relatively common in Swedes, but the low penetrances conferred by the risk alleles (genotype relative risks between 1.2 and 1.5) result in a limited contribution of the variants to the increased risk of bladder neoplasms among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking, occupational exposure to aromatic and heterocyclic amines, and probably chronic bladder infections are established risk factors for bladder cancer (Nordlund et al, 1997;Brennan et al, 2000Brennan et al, , 2001IARC, 2004;Gandini et al, 2008;Kiemeney et al, 2008). Variants in genes coding for xenobiotictransforming enzymes and polymorphisms in DNA repair genes may also modify cancer susceptibility (Easton et al, 2007;Kellen et al, 2007;Murta-Nascimento et al, 2007b;Sanderson et al, 2007;Andrew et al, 2008).…”
mentioning
confidence: 99%